Endothelial-Derived Interleukin-1α Activates Innate Immunity by Promoting the Bactericidal Activity of Transendothelial Neutrophils - Liu, Xiaoye; Zhang, Hui; He, Shangwen; Mu, Xiang; Hu, Ge; Dong, Hong (Frontiers in Cell and Developmental Biology, 2020)
Migration of neutrophils across endothelial barriers to capture and eliminate bacteria is served as the first line of innate immunity. Bacterial virulence factors damage endothelium to produce inflammatory cytokines interacts with neutrophils. However, the mechanisms that behind endothelial-neutrophil interaction impact on the bactericidal activity remain unclear. Therefore, we aimed to find the target proteins on endothelial cells that triggered the bactericidal activity of transendothelial neutrophils. Herein, we built the infected models on rats and endothelial-neutrophil co-cultural system (Transwell) and discovered that endothelial-derived IL-1α promoted the survival of rats under Escherichia coli infection and enhanced the bactericidal activity of transendothelial neutrophils in vivo and in vitro. Results further showed that IL-1α was inhibited by lipopolysaccharide (LPS) in the endothelial-neutrophil interaction. We found that LPS mainly damaged cell membrane and induced cell necrosis to interrupt neutrophil migration from endothelial barrier. Thus, we used the isobaric tags for relative and absolute quantification (iTRAQ) method to identify different proteins of endothelial cells. Results showed that IL-1α targeted cellular plasma membrane, endoplasmic reticulum and mitochondrial envelope and triggered eleven common proteins to persistently regulate. During the early phase, IL-1α triggered the upregulation of cell adhesion molecules (CAMs) to promote neutrophil adhesion, while oxidative phosphorylation was involved in long time regulation to induce transmigration of neutrophils against bacteria. Our results highlight the critical mechanism of endothelial-derived IL-1α on promoting bactericidal activity of transendothelial neutrophils and the findings of IL-1α triggered proteins provide the potentially important targets on the regulation of innate immunity.